Spermatozoal competition in common carp (Cyprinus carpio): what is the primary determinant of competition success? - Linhart, O; Rodina, M; Gela, D; Kocour, M; Vandeputte, M (Reproduction (Cambridge, England), 2005)
The percentage of sperm motility (92-100%), spermatozoan velocity (112-163 microm.s(-1)) and control hatching rates (83-96%) were evaluated for each of six gold and five green male common carp (Cyprinus carpio). In all 30 possible paired combinations of sperm-competition tests, hatching rates of 90-97% were achieved. The mean percentage of offspring sired was strongly influenced by the male used (P < 0.001, R2 = 0.91). The best male sired an average of 88% of the offspring in its competition tests, and the worst male sired only 5%. Spermatozoan-quality parameters could explain only part of the variation in male competitive ability. The male effects alone explained 91.4% of the observed variance, consisting of 17.1% explained by spermatozoan motility and 32.5% by control hatching rates in single fertilizations. Undetermined male effects explained 41.8%. The velocity of spermatozoa had no effect on the outcome of sperm competition. Neither was there any link between spermatozoan velocity and hatching rate in a control hatching test, whereas there was an effect of motility on hatching rate in this same test.
Keywords: fertilizace; počet spermií; zvířata; embryonální vývoj; Sperm Motility; mužské pohlaví; Sperm Count; Male; Animals; Fertilization; spermie; Carps; Embryonic Development; motilita spermií; kapři; Spermatozoa